A rare giant congenital intramural uterine cyst: a case report - Su, Ping; Wang, Ben; Liu, Su-wei; Yuan, Yi-ping; Han, Jian (Frontiers in Oncology, 2025)
Congenital intramural uterine cysts are extremely rare and often difficult to diagnose preoperatively. They are typically associated with remnants of the mesonephric or paramesonephric ducts and are pathologically benign; however, a very small number also carry a risk of malignancy. Imaging examinations can well aid in the diagnosis of uterine cysts, but because of their clinical rarity, the rate of misdiagnosis is very high. We report a case of a large congenital intramural uterine cyst. The preoperative ultrasound images showed a huge cyst in the pelvic area. The intraoperative images demonstrated the typical features of this case specimen: a cystic mass approximately 14 cm in diameter protruded from the left posterior wall of the uterus to the serous layer. Finally, we performed surgical resection of this cyst, and the pathology confirmed the diagnosis. Surgical treatment is the standard method for such cases.